Defining upstream enhancing and inhibiting sequence patterns for plant peroxisome targeting signal type 1 using large‐scale in silico and in vivo analyses. (19th June 2022) - Deng, Qianwen; Li, He; Feng, Yanlei; Xu, Ruonan; Li, Weiran; Zhu, Rui; Akhter, Delara; Shen, Xingxing; Hu, Jianping; Jiang, Hangjin; Pan, Ronghui
SUMMARY: Peroxisomes are universal eukaryotic organelles essential to plants and animals. Most peroxisomal matrix proteins carry peroxisome targeting signal type 1 (PTS1), a C‐terminal tripeptide. Studies from various kingdoms have revealed influences from sequence upstream of the tripeptide on peroxisome targeting, supporting the view that positive charges in the upstream region are the major enhancing elements. However, a systematic approach to better define the upstream elements influencing PTS1 targeting capability is needed. Here, we used protein sequences from 177 plant genomes to perform large‐scale and in‐depth analysis of the PTS1 domain, which includes the PTS1 tripeptide and upstream sequence elements. We identified and verified 12 low‐frequency PTS1 tripeptides and revealed upstream enhancing and inhibiting sequence patterns for peroxisome targeting, which were subsequently validated in vivo . Follow‐up analysis revealed that nonpolar and acidic residues have relatively strong enhancing and inhibiting effects, respectively, on peroxisome targeting. However, in contrast to the previous understanding, positive charges alone do not show the anticipated enhancing effect and that both the position and property of the residues within these patterns are important for peroxisome targeting. We further demonstrated that the three residues immediately upstream of the tripeptide are the core influencers, with a 'basic‐nonpolar‐basic' pattern serving as a strong and universal enhancing pattern for peroxisome targeting. These findings have significantly advanced our knowledge of the PTS1 domain in plants and likely other eukaryotic species as well. The principles and strategies employed in the present study may also be applied to deciphering auxiliary targeting signals for other organelles. Significance Statement: Large‐scale in silico and in vivo studies identified and validated low‐frequency peroxisome targeting signal type 1 tripeptides in plants and revealed enhancing and inhibiting sequence patterns upstream of the tripeptide for peroxisome targeting. The findings from the present study significantly advance our understanding of peroxisome targeting and similar strategies may be applied to elucidate auxiliary targeting signals for other organelles.